2018
DOI: 10.4018/978-1-5225-5273-4.ch014
|View full text |Cite
|
Sign up to set email alerts
|

A Contemporary Approach to Plan Independent Logistics Actors

Abstract: Companies are dependent on the resources and information of other members of the supply chains. To manage their resources, companies use coordination mechanisms. Despite the inter-dependency between logistics actors, they are independent units with conflicting objectives. These two characteristics can increase the complexity of planning in logistics networks. According to the literature of supply chain management, some mechanisms largely use the information shared by members to achieve an optimal solution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It is observed that with the support of a large number of documents, scholars have done a great deal of work on the applicability of the contract. The details from very simple models to very complex models are different, and coordination among multiple actors at different levels of the supply chain can be achieved through contract execution ( [42], [43]). The analysis of the contract implementation between supply chain members should pay more and more attention in theory and practice.…”
Section: Future Researchmentioning
confidence: 99%
“…It is observed that with the support of a large number of documents, scholars have done a great deal of work on the applicability of the contract. The details from very simple models to very complex models are different, and coordination among multiple actors at different levels of the supply chain can be achieved through contract execution ( [42], [43]). The analysis of the contract implementation between supply chain members should pay more and more attention in theory and practice.…”
Section: Future Researchmentioning
confidence: 99%